Comparative Genomics and Phylogenomic Analysis of the Genus Salinivibrio - de la Haba, Rafael R.; López-Hermoso, Clara; Sánchez-Porro, Cristina; Konstantinidis, Konstantinos T.; Ventosa, Antonio (Frontiers in Microbiology, 2019)
In the genomic era phylogenetic relationship among prokaryotes can be inferred from the core orthologous genes or proteins in order to elucidate their evolutionary history and current taxonomy should benefits of that. The genus Salinivibrio belongs to the family Vibrionaceae and currently includes only five halophilic species, in spite the fact that new strains are very frequently isolated from hypersaline environments. Species belonging to this genus have undergone several reclassifications and, moreover, there are many strains of Salinivibrio with available genomes which have not been affiliated to the existing species or have been wrongly designated. Therefore, a phylogenetic study using the available genomic information is necessary to clarify the relationships of existing strains within this genus and to review their taxonomic affiliation. For that purpose, we have also sequenced the first complete genome of a Salinivibrio species, Salinivibrio kushneri AL184T, which was employed as a reference to order the contigs of the draft genomes of the type strains of the current species of this genus, as well as to perform a comparative analysis with all the other available Salinivibrio sp. genomes. The genome of S. kushneri AL184T was assembled in two circular chromosomes (with sizes of 2.84 Mb and 0.60 Mb, respectively), as typically occurs in members of the family Vibrionaceae, with nine complete ribosomal operons, which might explain the fast growing rate of salinivibrios cultured under laboratory conditions. Synteny analysis among the type strains of the genus revealed a high level of genomic conservation in both chromosomes, which allow us to hypothesize a slow speciation process or homogenization events taking place in this group of microorganisms to be tested experimentally in the future. Phylogenomic and Orthologous Average Nucleotide Identity (OrthoANI)/Average Amino acid Identity (AAI) analyses also evidenced the elevated level of genetic relatedness within members of this genus and allowed to group all the Salinivibrio strains with available genomes in seven separated species. Genome-scale attribute study of the salinivibrios identified traits related to polar flagellum, facultatively anaerobic growth and osmotic response, in accordance to the phenotypic features described for species of this genus.